2003
DOI: 10.1093/ps/82.7.1188
|View full text |Cite
|
Sign up to set email alerts
|

Effect of feeding time on the reproductive performance of Japanese quail (Coturnix coturnix japonica)

Abstract: Several feeding regimens are applied to improve performance of fertile egg production during times of heat stress. During a period of heat stress (34 to 36 degrees C), two feeding periods were used to measure the impact of feeding time on reproductive performance of Japanese quail (Coturnix cotunix japonica) between 44 and 60 wk of age. Each feeding time treatment had 25 individually caged male and female pairs. Quail were fed ad libitum between 0600 to 1400 or 1400 to 2200 h daily. Results indicated that feed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
8
2
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 26 publications
6
8
2
1
Order By: Relevance
“…These values are close to those observed by Santos et al (2011), who obtained an average fertility of 98.15% in 120-d-old quail breeders. Hassan et al (2003) evaluated quails with approximately 310 days of age and found a fertility value of 72.10%, lower than found herein, even in the treatments with higher age (270 days). Dere et al (2009) reported no fertility differences in eggs from breeders with 90 and 180 days, with values of 82.01% and 81.7%, respectively.…”
Section: Influence Of European Quail Breeders Age On Egg Quality Inccontrasting
confidence: 65%
“…These values are close to those observed by Santos et al (2011), who obtained an average fertility of 98.15% in 120-d-old quail breeders. Hassan et al (2003) evaluated quails with approximately 310 days of age and found a fertility value of 72.10%, lower than found herein, even in the treatments with higher age (270 days). Dere et al (2009) reported no fertility differences in eggs from breeders with 90 and 180 days, with values of 82.01% and 81.7%, respectively.…”
Section: Influence Of European Quail Breeders Age On Egg Quality Inccontrasting
confidence: 65%
“…Em outro estudo, Santos et al (2011) descreveram uma fertilidade superior para codornas de 120 dias de idade, com média de 98,15%. Já em grupos de matrizes mais velhas, com aproximadamente 310 dias de idade, Hassan et al (2003) encontraram valores de fertilidade de 72,1%, valores inferiores aos encontrados no presente experimento. Na análise da camada perivitelínica de ovos férteis foram observadas concreções minerais.…”
Section: Discussionunclassified
“…The development of quail culture has led farmers to rear both meatand egg-type quail breeders, which has demanded studies on the reproductive management of this species. General data on the ideal male-to-female ratios, hatching egg storage time, correlation between egg weight and fertility rate, hatchability (Bacon & Nestor, 1975;Narahari et al, 1988;Kobayashi et al, 1994;Adkins-Regan, 1995;Petek et al, 2003;Hassan et al, 2003), and fertility duration (Sittman & Abplanalp, 1965;Reddish et al, 1996) have been described for egg-type quails.…”
Section: Introductionmentioning
confidence: 99%